Use of a modified AFLP protocol to discriminate Salmonella enterica subsp.enterica serovar Enteritidis isolates - Vaz, Clarissa Silveira Luiz; Streck, André Felipe; Tramontina, Tatiana; Cardoso, Marisa Ribeiro de Itapema; Canal, Cláudio Wageck (Acta Scientiae Veterinariae, 2018)
Salmonella enterica subsp. enterica (S.) serovar Enteritidis is one of the main pathogens involved in food-borne diseases worldwide. In epidemiological investigations of food-related salmonellosis, subtyping is necessary to improve preventive and control measures. Single-enzyme amplified fragment length polymorphism (SE-AFLP) analysis is a modified AFLP that uses only one restriction enzyme to produce DNA fragments that are selectively amplified by PCR. In order to assess the applicability of SE-AFLP in S. Enteritidis typing, one hundred and eight strains isolated from poultry, swine and also from human salmonellosis outbreaks in Southern Brazil were analyzed. Strains from other countries and six different S. enterica serovars were also included as controls. SE-AFLP was able to distinguish S. Enteritidis from the other S. enterica serovars analyzed. However, most of S. Enteritidis strains isolated from poultry, salmonellosis outbreaks and most of the strains from other countries shared the same predominant pattern. The low genetic diversity identified in S. Enteritidis suggests that the strains analyzed are clonally related and one predominant SE-AFLP genotype is widely spread in Southern Brazil.